2021
DOI: 10.1093/cercor/bhab283
|View full text |Cite
|
Sign up to set email alerts
|

Small Nucleus Accumbens and Large Cerebral Ventricles in Infants and Toddlers Prior to Receiving Diagnoses of Autism Spectrum Disorder

Abstract: Early interventions for autism spectrum disorder (ASD) are increasingly available, while only 42–50% of ASD children are diagnosed before 3 years old (YO). To identify neuroimaging biomarkers for early ASD diagnosis, we evaluated surface- and voxel-based brain morphometry in participants under 3YO who were later diagnosed with ASD. Magnetic resonance imaging data were retrospectively obtained from patients later diagnosed with ASD at Boston Children’s Hospital. The ASD participants with comorbidities such as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
2
8
0
Order By: Relevance
“…Specifically, changes in the brain have been observed in infants at risk for ASD under 2 years of age (e.g., Wolff et al, 2012 ; Hazlett et al, 2017 ), preceding clinical manifestations. The changes in brain were also reported for infants under 2 years of age later developing ASD and identified through retrospective study (e.g., Levman et al, 2018 , 2019 ; Shiohama et al, 2021 ). A machine learning model that leverages sensitive imaging biomarkers may be capable of predicting the clinical diagnostic outcome of individual infants before the development of the full syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, changes in the brain have been observed in infants at risk for ASD under 2 years of age (e.g., Wolff et al, 2012 ; Hazlett et al, 2017 ), preceding clinical manifestations. The changes in brain were also reported for infants under 2 years of age later developing ASD and identified through retrospective study (e.g., Levman et al, 2018 , 2019 ; Shiohama et al, 2021 ). A machine learning model that leverages sensitive imaging biomarkers may be capable of predicting the clinical diagnostic outcome of individual infants before the development of the full syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, nearly all the current literature on brain structure and function in ASD focuses on late childhood periods after 7 years of age (e.g., Keown et al, 2013 ; Supekar et al, 2013 ; Payabvash et al, 2019 ), or adolescent and adult groups (e.g., Rudie et al, 2013 ; Di Martino et al, 2014 ; Nomi and Uddin, 2015 ). Recently, a few retrospective neuroimaging studies included very young children before 2–3 years who went on to be diagnosed with ASD ( Levman et al, 2018 , 2019 ; Shiohama et al, 2021 ). Diffusion MRI studies on the important early developmental period of 2–7 years in ASD are relatively scarce and were conducted to investigate white matter microstructural changes (e.g., Ben Bashat et al, 2007 ; Walker et al, 2012 ; Ouyang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, less thickness has been identified in the caudal anterior cingulate cortex and greater thickness in the right medial orbitofrontal cortex. These factors are independent of age, gender, and gestational age, suggesting that there are magnetic resonance imaging biomarkers that can predict the development of ASD, and that can help in a better diagnosis of the disorder [53].…”
Section: New Concepts Of Asd Neuropathologymentioning
confidence: 99%
“…Significant changes in volume and neuronal density were reported in the DS ( 13 ). Also, a significantly smaller bilateral VS and larger cerebral ventricles were identified in individuals with a later diagnosis of ASD ( 14 ). In mice, it has also been observed that chemogenetic inhibition of dopaminergic neurons in the VTA leads to reduced exploration of novel social stimuli ( 15 ).…”
Section: Introductionmentioning
confidence: 99%